Gay men as parents: Analysing resistant talk in South African mainstream media accounts of queer families. (May 2016) - Lynch, Ingrid; Morison, Tracy
There is increasing visibility of dissident sexualities and genders in media debates about families, including resistant discourses that challenge delegitimising claims about queer families. There remains, however, a lack of research that assesses the ways in which discourses seeking to defend queer parenthood function to challenge or, at times, reinforce hetero-gendered norms. Families formed by gay men have generally received less attention, both in the media as well as academic scholarship. In this paper, we explore resistant discourses deployed in mainstream print media, attending particularly to news reports about queer fathers and their children. Through a critical thematic analysis of South African newspapers, informed by feminist discursive psychology, we identify four themes in resistant ways of talking: de-gendering parenthood, normalising queer parents, valorising queer parenting, and challenging the heteronormative gold standard. We conclude with the political implications of such resistant talk, as part of a project of transforming restrictive hetero-gendered norms.